Hsa_circ_0000437 upregulates and promotes disease progression in rheumatic valvular heart disease. Issue 2 (24th December 2021) - Zhu, Linwen; Wang, Zhifang; Sun, Lebo; Zheng, Dawei; Hu, Bingchuan; Li, Ni; Shao, Guofeng
Abstract: Background: Currently, the diagnosis and outcome of rheumatic valvular heart disease (RVHD) are less than ideal, and there are no accurate biomarkers. Circular RNA (circRNA) might participate in the occurrence and development of RVHD. Materials and methods: We use circRNA microarray to filter out the target has_circ_0000437. qRT‐PCR was used to measure the expression levels of hsa_circ_0000437 in RVHD plasma samples. We assessed the diagnostic value of hsa_circ_0000437 in RVHD. Cell function in vitro experiment was to explore the effect of has_circ_0000437 on RVHD. Results: Has_circ_0000437 is highly expressed in RVHD ( p  < 0.001). has_circ_0000437 has the diagnostic value in RVHD. In RVHD, hsa_circ_0000437 can promote cell proliferation and migration but inhibits its apoptosis. This may be due to the combination of has_circ_0000437 and target miRNA in the cytoplasm that affects the progress of RVHD. Conclusions: Has_circ_0000437 can promote the process of RVHD and may be a potential for the diagnosis and treatment of RVHD. Abstract : Apoptotic cell rate of hVICs cells following downregulation of hsa_circ_0000437. (B) Apoptotic cell rate of HVICS cells following upregulation of hsa_circ_0000437. (C) Cell‐cycle distribution of hVICs cells following downregulation of hsa_circ_0000437. (D) Cell‐cycle distribution of hVICs cells following upregulation of hsa_circ_0000437. NC, negative control; KO, knockout; n  = 3, * p  < 0.05, *** p  < 0.001.